THE AUTHORITY OF THE TEMPORARY HEAD OF VILLAGE IN SILANGGE VILLAGE GOVERNMENT SYSTEM, DOLOK DISTRICT, NORTH PADANG LAWAS REGENCY - Muhammad Juang Rambe (CERED Indonesia Institute, 2021)
The appointment of the Silangge village head official was due to the permanent dismissal of the previous village head who died, then the District Head. North Padang Lawas appointed the sub-district head of Dolok sub-district as a temporary office in Silangge Village, district. Dolok Kab. North Padang Lawas until 2016. The approach method used to research the discussion of this thesis is an empirical juridical approach, namely the research in this thesis was carried out by field studies at the Dolok Subdistrict Head Office, North Padang Lawas Regency. This study was carried out concerning the applicable laws and regulations. The Temporary Village Head's authority in running the Silangge village administration is the same as the village head, the Silangge Temporary Village Head in 2013 has the main task of carrying out village head elections, then the next Silangge Village Head in 2015 also has the main task of organizing village head election. The term of office of the Silangge Village Head from 2015 to 2016 carried out village infrastructure development through village funds in 2015 and 2016 and carried out the Silangge village head election in 2016.The Authority of the Temporary Head of Village in Silangge Village Government System, Dolok District, North Padang Lawas Regency